2007
DOI: 10.1103/physrevstab.10.073501
|View full text |Cite
|
Sign up to set email alerts
|

First application of a tungsten single-crystal positron source at the KEK B factory

Abstract: A new tungsten single-crystal target has been successfully employed at the positron source of the KEKB injector linac. The crystal thickness was determined to be 10.5 mm based on previous systematic measurements of the positron-production efficiency. The crystal axis, h111i, was precisely aligned to the direction of the 4-GeV primary electron beam. The positron yield increased by 25% compared to that for a conventional tungsten plate with a thickness of 14 mm. On the contrary, the steady-state heat load on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An axially oriented tungsten (W) crystal serving at the same time as the radiator and converter was used at the KEKB factory in Ref. [17]. An advanced method, the so-called hybrid positron source, was proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An axially oriented tungsten (W) crystal serving at the same time as the radiator and converter was used at the KEKB factory in Ref. [17]. An advanced method, the so-called hybrid positron source, was proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Since the axial continuous potential is mostly deeper than the planar one, axial CR in a W crystal was preferred to the planar one in Refs. [17][18][19][20][21]. Therefore, we also restrict our calculations to a W single-crystal radiator, because, due to its large atomic number, the CR yield is expected to be larger than that for diamond, Si, or Ge crystals.…”
Section: Introductionmentioning
confidence: 99%
“…These photons can, then, materialize into e-e+ pairs in the same crystal or in amorphous converters put downstream. Theoretical studies [1] and simulations [2][3][4] were confirmed by experiments at CERN and KEK [5][6][7][8][9]. Separating the crystal-radiator from the amorphous-converter with a bending magnet in between to sweep off the charged particles, allowing only photons to impinge on the converter, presents very interesting features concerning the amount of energy deposited and for its density.…”
Section: -Introductionmentioning
confidence: 71%
“…The target intensity of the GF source of electrons/positrons is 10 17 leptons s −1 , assuming the present CERN accelerator infrastructure and presently available laser technology. Such intensity, if achieved, would be three orders of magnitude higher than that of the KEK positron source, [ 499 ] and would largely satisfy the positron/electron source requirements for the proposed future high‐luminosity and high‐energy ep$ep$ (eA$eA$) collider project. [ 500 ]…”
Section: Nuclear Physics With Tertiary Beamsmentioning
confidence: 99%